Synergistic Exfoliation of MoS2 by Ultrasound Sonication in a Supercritical Fluid Based Complex Solvent - Xi Tan; Wenbin Kang; Jingfeng Liu; Chuhong Zhang (Nanoscale Research Letters, 2019)
Abstract Molybdenum disulfide (MoS2) is an extremely intriguing low-D layered material due to its exotic electronic, optical, and mechanical properties, which could be well exploited for numerous applications to energy storage, sensing, and catalysis, etc., provided a sufficiently low number of layers is achieved. A facile exfoliation strategy that leads to the production of few-layered MoS2 is proposed wherein the exfoliation efficacy could be synergistically boosted to > 90% by exploiting ultrasound sonication in supercritical CO2 in conjunction with N-methyl-2-pyrrolidone (NMP) as the intercalating solvent, which is superior to general practiced liquid exfoliation methods wherein only the supernatant is collected to avoid the majority of unexfoliated sediments. The facile and fast exfoliation technique suggests an exciting and feasible solution for scalable production of few-layered MoS2 and establishes a platform that contributes to fulfilling the full potential of this versatile two-dimensional material.